Reviewing Accuracy of First Trimester Screening for Preeclampsia Using Maternal Factors and Biomarkers - Malone SL; Haj Yahya R; Kane SC (Dove Medical Press, 2022)
Sarah L Malone,1 Rani Haj Yahya,1 Stefan C Kane1,2 1Department of Maternal Fetal Medicine, the Royal Women's Hospital, Parkville, Victoria, Australia; 2The University of Melbourne, Department of Obstetrics and Gynaecology, Parkville, Victoria, AustraliaCorrespondence: Sarah L Malone, Department of Maternal Fetal Medicine, the Royal Women's Hospital, Parkville, Victoria, Australia, Tel +61 3 8345 2000, Email Sarah.Malone@thewomens.org.auAbstract: Preeclampsia is a common and important complication of pregnancy, one with potentially significant morbidity and even mortality to both mother and baby. Identifying those at high risk of developing the condition is helpful as there is evidence that the incidence of preeclampsia can be reduced with low dose aspirin taken in pregnancy. Accurately predicting the risk of preeclampsia allows for more targeted aspirin prophylaxis and a greater opportunity for early detection of maternal and/or fetal complications associated with impaired placentation through a schedule of enhanced antenatal surveillance. Traditional preeclampsia prediction models use maternal characteristics and risk factors and have been shown to be of low predictive value. Multiparametric screening tests combine patient characteristics with serum biomarkers and ultrasound Doppler indices and have been shown to be more effective at detecting those at high risk of preeclampsia - more specifically, early-onset preeclampsia (onset of preeclampsia < 34 weeks' gestation). Multiparametric screening has now been validated in different populations. The true cost effectiveness of a multiparametric screening model for preeclampsia screening is not yet fully known and will vary depending on the clinical setting. Despite the growing body of evidence for its improved detection rates, first trimester preeclampsia screening using multiparametric models is not widely implemented and is not part of the recommendations for antenatal screening from most international bodies. The International Federation of Gynecology and Obstetrics has advised universal preeclampsia screening using maternal risk factors and biomarkers and has strongly encouraged its promotion worldwide. Various barriers to implementation must be considered such as the immediate cost of equipment and training, the need for audit and quality control, and the expected benefit to the population. Low to middle income settings may require a pragmatic approach to the implementation of multiparametric screening given limited resources.Keywords: preeclampsia, hypertensive disorders of pregnancy, screening, first trimester, serum biomarkers, ultrasound